Detection of cavitated approximal surfaces using cone beam CT and intraoral receptors - Wenzel, A.; Hirsch, E.; Christensen, J.; Matzen, L. H.; Scaf, G. [UNESP]; Frydenberg, M. (Oxford University Press (OUP), 2013)
Objectives: The aim of this study was to compare cone beam CT (CBCT) in a small field of view (FOV) with a solid-state sensor and a photostimulable phosphor plate system for detection of cavitated approximal surfaces. Methods: 257 non-filled approximal surfaces from human permanent premolars and molars were recorded by two intraoral digital receptors, a storage phosphor plate (Digora Optime, Soredex) and a solid-state CMOS sensor (Digora Toto, Soredex), and scanned in a cone beam CT unit (3D Accuitomo FPD80, Morita) with a FOV of 4 cm and a voxel size of 0.08 mm. Image sections were carried out in the axial and mesiodistal tooth planes. Six observers recorded surface cavitation in all images. Validation of the true absence or presence of surface cavitation was performed by inspecting the surfaces under strong light with the naked eye. Differences in sensitivity, specificity and agreement were estimated by analysing the binary data in a generalized linear model using an identity link function. Results: A significantly higher sensitivity was obtained by all observers with CBCT (p,0.001), which was not compromised by a lower specificity. Therefore, a significantly higher overall agreement was obtained with CBCT (p,0.001). There were no significant differences between the Digora Optime phosphor plate system and the Digora Toto CMOS sensor for any parameter. Conclusions: CBCT was much more accurate in the detection of surface cavitation in approximal surfaces than intraoral receptors. The differences are interpreted as clinically significant. A CBCT examination performed for other reasons should also be assessed for approximal surface cavities in teeth without restorations. © 2013 The British Institute of Radiology.
Keywords: Computed tomography; Dental caries; Diagnosis; Digital; Radiography; comparative study; cone beam computed tomography; dental caries; human; instrumentation; molar tooth; premolar tooth; radiography; sensitivity and specificity; statistical model; tooth radiography; validation study; Bicuspid; Cone-Beam Computed Tomography; Dental Caries; Humans; Linear Models; Molar; Radiography, Dental, Digital; Sensitivity and Specificity